Growth monitoring and promotion service utilization and its associated factors among children less than two years in Ethiopia: A systematic review and meta-analysis. - Mulat Belay Simegn; Werkneh Melkie Tilahun; Elyas Melaku Mazengia; Aysheshim Belaineh Haimanot; Anteneh Lamesgen Mneneh; Muluye Gebrie Mengie; Bekalu Endalew; Molla Yigzaw Birhanu; Tigabu Kidie Tesfie; Lakew Asmare; Habtamu Geremew (PLoS ONE)
Introduction Growth monitoring and promotion services are strategies to promote child health and reduce child mortality. Even though Ethiopia is attempting different strategies to cope with the low rate of GMP utilization, the problem is still unresolved. Objective Determine the pooled proportion of GMP utilization and its contributing factors among children less than two years in Ethiopia. Method The review protocol was registered with PROSPERO, number CRD42023472746. The PRISMA-2020 statement guided the conduct of this review. Electronic databases and grey literature were used. Heterogeneity was evaluated using I2. Subgroup analysis was conducted. The random effect model was used to summarize the pooled effect sizes with their respective 95% CI with STATA version 17. To test the small study effect, the funnel plot and Egger's test were applied. Result A total of seven (7) studies with 4027 participants were considered in this meta-analysis. The pooled proportion of GMP utilization reported by seven studies was 25.71% (95%CI: 24.39, 27.04). ANC follow-up (AOR = 2.11; 95% CI: 1.47, 2.76), PNC follow-up (AOR = 1.96; 95% CI: 1.44, 2.49), counseling (AOR = 2.88; 95% CI: 2.09, 3.68), maternal education (AOR = 2.89; 95% CI: 1.66, 4.13), paternal education (AOR = 3.78; 95% CI: 2.25, 5.32), family health card (AOR = 2.31; 95% CI: 1.67, 2.96), and mothers good knowledge towards GMP (AOR = 2.90; 95% CI: 1.72, 4.07) variables were positively associated with GMP service utilization. Conclusion and recommendation The pooled proportion of GMP remains low in Ethiopia. ANC and PNC follow-up, counseling, maternal and paternal education, family health cards, maternal knowledge towards GMP were significantly associated. Findings are essential for evidence-based policy making, intervention, and input for ongoing research.